2021
DOI: 10.14744/eej.2021.52244
|View full text |Cite
|
Sign up to set email alerts
|

Microbial contamination comparison between cotton pellet and polytetrafluoroethylene tape endodontic spacers: a systematic review

Abstract: This systematic review compares polytetrafluoroethylene tape and cotton pellet when used as endodontic spacers underneath provisional restorations. The review followed the PRISMA guidelines and was registered in the PROSPERO database (CRD42020176555). Studies that compared the microbial contamination between polytetrafluoroethylene tape and cotton pellet, when used as spacers, were included. Literature searches of Pubmed, Embase, EBSCOHost Dentistry & Oral Sciences Source, Scopus, and Open Grey databases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…A recent survey found that the majority of dentists in Saudi Arabia use the same temporization techniques taught in dental schools [ 58 ]. Teflon spacers were found to be a better alternative to cotton pellets [ 59 , 60 ]. However, cavit restoration is only used for less than two weeks and deteriorates easily under masticatory forces [ 56 , 57 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey found that the majority of dentists in Saudi Arabia use the same temporization techniques taught in dental schools [ 58 ]. Teflon spacers were found to be a better alternative to cotton pellets [ 59 , 60 ]. However, cavit restoration is only used for less than two weeks and deteriorates easily under masticatory forces [ 56 , 57 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, in the present study, cotton pellets were used as endodontic spacers and to wipe off excess medicaments from the access cavity walls. This step might leave residual cotton fibres on the access cavity walls, and can interrupt the seal of the temporary restoration as well as acting as a potential substrate for surviving bacteria [ 34 ]. Secondly, the procedures were performed without the aid of an endodontic microscope.…”
Section: Discussionmentioning
confidence: 99%
“…• Sintomática: Se caracteriza por momentos de dolor espontáneo, intermitente o continuo, de intensidad moderada o grave, punzante o apagado, localizado o referido. El proceso inflamatorio puede desencadenar una necrosis pulpar (Bernal-Treviño et al, 2018;Mathew et al, 2021;Milagros et al, 2018).…”
Section: Patologías Pulparesunclassified